2023
DOI: 10.1084/jem.20221007
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages promote anti-androgen resistance in prostate cancer bone disease

Abstract: Metastatic castration-resistant prostate cancer (PC) is the final stage of PC that acquires resistance to androgen deprivation therapies (ADT). Despite progresses in understanding of disease mechanisms, the specific contribution of the metastatic microenvironment to ADT resistance remains largely unknown. The current study identified that the macrophage is the major microenvironmental component of bone-metastatic PC in patients. Using a novel in vivo model, we demonstrated that macrophages were critical for en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 101 publications
1
25
0
Order By: Relevance
“…177 Lu-PSMA-617 therapy is almost always preferred in mCRPC with predominant bone metastases, and the findings in our study are consistent with studies revealing that macrophages, which are transformed from monocytes, are the most important key stromal cell type in bone metastatic PC. [32] In the present study, when the values before the treatment and after the 4th cycle of 177 Lu-PSMA-617 were compared, there was no significant decrease in the number of monocytes while the other peripheral blood cells decreased. Consistent with this, while no change was found in other inflammation indices, a significant increase was observed in MLR (Table 2).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…177 Lu-PSMA-617 therapy is almost always preferred in mCRPC with predominant bone metastases, and the findings in our study are consistent with studies revealing that macrophages, which are transformed from monocytes, are the most important key stromal cell type in bone metastatic PC. [32] In the present study, when the values before the treatment and after the 4th cycle of 177 Lu-PSMA-617 were compared, there was no significant decrease in the number of monocytes while the other peripheral blood cells decreased. Consistent with this, while no change was found in other inflammation indices, a significant increase was observed in MLR (Table 2).…”
Section: Discussionmentioning
confidence: 45%
“…[33] In another study, it was reported that monocyte-derived and bone-resident macrophages and some cytokines released from macrophages are the main causes of treatment resistance in mCRPC, especially in patients using abiraterone or enzalutamide. [32,34] Therefore, macrophages and some cytokines secreted by macrophages may be targets for mCRPC therapy., [32,33] In patients who exhibit resistance to androgen receptor signaling inhibitors and/or 177 Lu–PSMA-617 treatment, if inflammation indices such as NLR, MLR, PLR, and SII are high, it may be prudent to consider these patients as potential candidates for novel treatment strategies targeting macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor‐associated macrophages (TAMs) have been causally linked to PCa growth and progression—however, these are extremely plastic cells and can have diverse functions based on their stimuli 156–158 . M2 macrophages polarized by Th2‐derived cytokines like IL‐4/10/13, TGF‐β, or prostaglandin E2 have a wound‐healing response 159,160 . Conversely, M1‐polarized macrophages are activated by IFN‐γ and TNF‐α from Th1‐helper cells and produce proinflammatory cytokines, like IL‐1β, TNF, IL‐12, and IL‐18, and engage in direct or indirect tumor‐killing activity 161,162 .…”
Section: Immunosuppressive Niches Of the Tme Of Crpcmentioning
confidence: 99%
“…[1] In prostate cancer (PCa), TAMs are major immune cells in the tumor microenvironment to facilitate PCa progression via enhancing PCa cell migration and metastasis, promoting drug resistance, and so on. [2][3][4][5][6] Functionally, TAMs are primarily composed of M2-type macrophages, which can be polarized by various tumor microenvironmental factors such as chemokines, cytokines and tumor-derived extracellular vesicles (EVs). [7,8] Currently, besides their promoting effects on resistance of chemotherapy and immunotherapy, TAMs are reported to be also involved in the resistance of ferroptosis by secretion of transforming growth factor beta 1.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] In prostate cancer (PCa), TAMs are major immune cells in the tumor microenvironment to facilitate PCa progression via enhancing PCa cell migration and metastasis, promoting drug resistance, and so on. [ 2–6 ] Functionally, TAMs are primarily composed of M2‐type macrophages, which can be polarized by various tumor microenvironmental factors such as chemokines, cytokines and tumor‐derived extracellular vesicles (EVs). [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%